'It's on my iPhone': attitudes to the use of mobile computing devices in medical education, a mixed-methods study. Issue 4 (24th August 2012) - Wallace, Sean; Clark, Marcia; White, Jonathan
Abstract : Objective: The last decade has seen the introduction of new technology which has transformed many aspects of our culture, commerce, communication and education. This study examined how medical teachers and learners are using mobile computing devices such as the iPhone in medical education and practice, and how they envision them being used in the future. Design: Semistructured interviews were conducted with medical students, residents and faculty to examine participants' attitudes about the current and future use of mobile computing devices in medical education and practice. A thematic approach was used to summarise ideas and concepts expressed, and to develop an online survey. A mixed methods approach was used to integrate qualitative and quantitative findings. Setting and participants: Medical students, residents and faculty at a large Canadian medical school in 2011. Results: Interviews were conducted with 18 participants (10 students, 7 residents and 1 faculty member). Only 213 participants responded to the online survey (76 students, 65 residents and 41 faculty members). Over 85% of participants reported using a mobile-computing device. The main uses described for mobile devices related to information management, communication and time management. Advantages identified were portability, flexibility, access to multimedia and the ability to look up information quickly. Challenges identified included: superficial learning, not understanding how to find good learning resources, distraction, inappropriate use and concerns about access and privacy. Both medical students and physicians expressed the view that the use of these devices in medical education and practice will increase in the future. Conclusions: This new technology offers the potential to enhance learning and patient care, but also has potential problems associated with its use. It is important for leadership in medical schools and healthcare organisations to set the agenda in this rapidly developing area to maximise the benefits of this powerful new technology while avoiding unintended consequences.